+0  
 
-1
59
1
avatar

how does this 6 (4x -3) add 7 (x add 1) equel this 9 show working

Guest Jun 22, 2018
 #1
avatar
0

6(4x-3) + 7(x+1) = 9

 

(24x-18) + (7x+7) = 9

 

31x - 11 = 9

 

31x = 20

 

x = 20/31

Guest Jun 23, 2018

43 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.